Local spatial distribution of stream macroalgae – does gastropod activity matters? - Tonetto, Aurélio Fajar [UNESP]; Branco, Ciro Cesar Zanini [UNESP] (Schweizerbart, 2021)
The effects of gastropod Biomphalaria sp. on the benthic algae community (micro and macroalgae) were experimentally studied in an unshaded artificial stream. Using artificial substrates, two treatments were tested: with herbivores and without herbivores. The substrates remained submerged for 50 days, and the environmental and biological variables (algal abundance and richness) were obtained on days 7, 15, 30, 40 and 50 after the experiment has been installed. Repeated measure analyses of variance were applied to verify possible differences of chlorophyll-a content, species richness, microalgal density and macroalgal density and percent cover between treatments at each date. Results showed that herbivory pressure reduces significantly all measured biotic variables except algal rich-ness. Higher presence of macroalgae was related to a higher presence of microalgae in the substrates, indicating a potential relationship between these components. Thus, it seems that herbivore activity over microalgal biomass may have an indirect and negative effect on macroalgae, so that a reduction in microalgal density by grazing may have led to a corresponding decrease in abundance of macroalgae. Thus, the results suggest that the establishment and development of macroalgae in lotic environments can be regulated by a top-down cascade effect, in which the action of herbivores, herein the scraper Biomphalaria sp., on microalgae indirectly impacts the abundance of macroalgae.
Keywords: Herbivory; Macroalgae; Microalgae; Streams; Top-down control